Meningkatkan Hasil Belajar Matematika Materi Penjumlahan Pecahan Menggunakan Model Problem Based Learning Pada Siswa Kelas IV SDN Rumintin 1 Kabupaten Tapin - Aisyah, Aisyah; Sunarno, Sunarno (CV. ITTC INDONESIA, 2024)
The existence of classroom action research (PTK) in mathematics learning about adding fractions occurred because student learning outcomes were still low, so this research was carried out in 2 cycles. This research was carried out in the even semester of the 2023/2024 academic year in class IV at SDN Rumintin 1. The subjects in this research were 27 fourth grade students, consisting of 19 male students and 8 female students. The results of the research showed that there was an improvement in teacher activity so that in cycle I and cycle II student activity was at the